Overexpression of the NMig1 Gene Encoding a NudC Domain Protein Enhances Root Growth and Abiotic Stress Tolerance in Arabidopsis thaliana - Velinov, Valentin; Vaseva, Irina; Zehirov, Grigor; Zhiponova, Miroslava; Georgieva, Mariana; Vangheluwe, Nick; Beeckman, Tom; Vassileva, Valya (Frontiers in Plant Science, 2020)
The family of NudC proteins has representatives in all eukaryotes and plays essential evolutionarily conserved roles in many aspects of organismal development and stress response, including nuclear migration, cell division, folding and stabilisation of other proteins. This study investigates an undescribed Arabidopsis homolog of the Aspergillus nidulans NudC gene, named NMig1 (for Nuclear Migration 1), which shares high sequence similarity to other plant and mammalian NudC-like genes. Expression of NMig1 was highly upregulated in response to several abiotic stress factors, such as heat shock, drought and high salinity. Constitutive overexpression of NMig1 led to enhanced root growth and lateral root development under optimal and stress conditions. Exposure to abiotic stress resulted in relatively weaker inhibition of root length and branching in NMig1-overexpressing plants, compared to the wild-type Col-0. The expression level of antioxidant enzyme-encoding genes and other stress-associated genes was considerably induced in the transgenic plants. The increased expression of the major antioxidant enzymes and greater antioxidant potential correlated well with the lower levels of reactive oxygen species (ROS) and lower lipid peroxidation. In addition, the overexpression of NMig1 was associated with strong upregulation of genes encoding heat shock proteins and abiotic stress-associated genes. Therefore, our data demonstrate that the NudC homolog NMig1 could be considered as a potentially important target gene for further use, including breeding more resilient crops with improved root architecture under abiotic stress.